PIC simulation of low-frequency modulation of supercritical electron beam at plasma assstancei - Markov, P.I.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2005)
The results of simulations of virtual cathode dynamics at the presence of plasma are presented. The theoretical analysis of dynamics of the electron-ion formation is based on particle-in-cell method (PIC). Numerical calculations are carried out for the modernized experimental installation "Agate" with intense relativistic electron beam. It is shown that an output electron beam current has a strong temporal modulation. The modulating frequency at injection of hydrogen ions is about 300 MHz.